TEACHER AND LEARNERS’ TALK DURING CLASSROOM INTERACTION - Lovita Uli Simbolon; Sri Menti Br Pinem; Fitri Devi Enjelina Silitonga (English Language Teaching Prima Journal (ELT), 2019)
This study discussed about Students’ and learners’ Talk during classroom interaction. This study was conducted at SMK Telkom 2 Medan. This study used descriptive qualitative research as research design. The instrument used in this research were observation and interview. From the analysis of the data, it was found that there were some categories of classroom interaction, especially in the pattern of talk. Communication performed by the English teachers and their students were still using mix language between English and Indonesia. In performing the communication, the English teachers produced twelve categories of talk while their students produced four categories of talk. Key Words, Teachers, Students, Talk